KINERJA GURU DAN FAKTOR YANG MEMPENGARUHINYA - Cahyo Harry Sancoko; Rini Sugiarti (STKIP ROKANIA, 2022)
Teacher performance continues to be in the spotlight in the world of education. Expectations for good teacher performance are what the community wants. With good teacher performance, it is hoped that it will produce quality students. This study aims to determine the performance of teachers and the factors that influence teacher performance. The study used the literature review method. There are 8 journal articles analyzed by the researcher. In this study, it was found that teacher performance was closely related to the learning activities they carried out. In general, it can be said that teacher performance is influenced by internal and external factors. Internal factors that affect teacher performance include motivation, positive emotions, negative emotions, responsibility for tasks, discipline in completing tasks, concern for students, and job satisfaction. While external factors that affect teacher performance include leadership style, work environment, evaluation and supervision mechanisms, information and communication technology facilities, and existing facilities in the school environment such as clean water, sanitation, electricity, and the condition of school buildings.